Chloroplast genomic insights into adaptive evolution and rapid radiation in the genus Passiflora (Passifloraceae) - Cauz Santos, Luiz Augusto (2025)
Chloroplasts are essential organelles in plants and eukaryotic algae, responsible for photosynthesis, fatty acid synthesis, amino acid production, and stress responses. The genus Passiflora, known for its species diversity and dynamic chloroplast (cp) genome evolution, serves as an excellent model for studying structural variations. This study investigates evolutionary relationships within Passiflora by sequencing 11 new chloroplast genomes, assessing selective pressures on cp genes, and comparing plastid and nuclear phylogenies. Passiflora cp genomes showed significant variations in size, gene content, and structure, ranging from 132,736 to 163,292 base pairs, especially in Decaloba. Structural rearrangements and species-specific repeat patterns were identified. Selective pressure tests revealed significant adaptive evolution in certain lineages, with several genes, including clpP and petL, under positive selection. Phylogenetic analyses confirmed the monophyly of subgenera Astrophea, Passiflora, and Decaloba, while Deidamioides appeared polyphyletic. Nuclear phylogenetic analysis based on 35S rDNA sequences supported the monophyly of Astrophea but showed inconsistencies within subgenus Passiflora compared to cp genome data. This study highlights the evolutionary complexity of Passiflora cp genomes, demonstrating significant structural variations and adaptive evolution. The findings underscore the effectiveness of plastid phylogenomics in resolving phylogenetic relationships and provide insights into adaptive mechanisms shaping cp genome diversity in angiosperms.